# |
ODE |
Mathematica |
Maple |
\[
{}\cos \left (\theta \right ) r^{\prime }-r \sin \left (\theta \right )+{\mathrm e}^{\theta } = 0
\] |
✓ |
✓ |
|
\[
{}y \,{\mathrm e}^{x y}-\frac {1}{y}+\left (x \,{\mathrm e}^{x y}+\frac {x}{y^{2}}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {1}{y}-\left (3 y-\frac {x}{y^{2}}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x +y^{2}-\cos \left (x +y\right )+\left (2 x y-\cos \left (x +y\right )-{\mathrm e}^{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {{\mathrm e}^{x +y}}{y-1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-4 y = 32 x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-\frac {2}{y^{3}}\right ) y^{\prime }+2 x y-3 x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {3 y}{x} = x^{2}-4 x +3
\] |
✓ |
✓ |
|
\[
{}2 x y^{3}-\left (-x^{2}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}t^{3} y^{2}+\frac {t^{4} y^{\prime }}{y^{6}} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = {\mathrm e}^{2 x}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y-x +1 = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \left (1+x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+2 x y = \sinh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{1-x}+2 x -x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{1-x}+x -x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = x y+1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x y = x y^{2}
\] |
✓ |
✓ |
|
\[
{}3 x y^{\prime }+y+x^{2} y^{4} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {2 y}{x}-x^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 y}{x}-x^{3} = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x^{2}+2 x -3
\] |
✓ |
✓ |
|
\[
{}\left (1+x \right )^{2} y^{\prime } = 1+y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = {\mathrm e}^{3 x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = x^{3} \sin \left (3 x \right )+4
\] |
✓ |
✓ |
|
\[
{}x \cos \left (y\right ) y^{\prime }-\sin \left (y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}\left (x y^{2}+x^{3}\right ) y^{\prime } = 2 y^{3}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime }+2 x y = x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \tanh \left (x \right ) = 2 \sinh \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-2 y = x^{3} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = y^{3}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+3 y = x^{2} y^{2}
\] |
✓ |
✓ |
|
\[
{}x \left (-3+y\right ) y^{\prime } = 4 y
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+1\right ) y^{\prime } = x^{2} y
\] |
✓ |
✓ |
|
\[
{}x^{3}+\left (1+y\right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right )+\left (1+{\mathrm e}^{-x}\right ) \sin \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (1+y\right )+y^{2} \left (x -1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (-x +2 y\right ) y^{\prime } = y+2 x
\] |
✓ |
✓ |
|
\[
{}x y+y^{2}+\left (x^{2}-x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{3}+x^{3} = 3 y^{2} y^{\prime } x
\] |
✓ |
✓ |
|
\[
{}y-3 x +\left (4 y+3 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+3 x y^{2}\right ) y^{\prime } = y^{3}+3 x^{2} y
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{3}+3 x^{2}-2 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\tan \left (x \right ) y = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = x^{3} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+3 x y = 5 x
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = 5 \,{\mathrm e}^{\cos \left (x \right )}
\] |
✓ |
✓ |
|
\[
{}\left (3 x +3 y-4\right ) y^{\prime } = -x -y
\] |
✓ |
✓ |
|
\[
{}-x y^{2}+x = \left (x +x^{2} y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x -y-1+\left (4 y+x -1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y-7 x +7+\left (7 y-3 x +3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (x y+1\right )+x \left (1+x y+x^{2} y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = x y^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = y^{4} {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime }+y = y^{3} \left (x -1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 \tan \left (x \right ) y = y^{2} \tan \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\tan \left (x \right ) y = y^{3} \sec \left (x \right )^{4}
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime } = x y+1
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime }-\left (1+x \right ) \sqrt {y-1} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}-2 x y+5 y^{2} = \left (y^{2}+2 x y+x^{2}\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y \cot \left (x \right ) = y^{2} \sec \left (x \right )^{2}
\] |
✓ |
✓ |
|
\[
{}y+\left (x^{2}-4 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\tan \left (x \right ) y = \cos \left (x \right )-2 x \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x y+y^{2}}{x^{2}+2 x y}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime } = x \left (1+y\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+2 y = 3 x -1
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = y^{2}-x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{3 x -2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{2}+x^{2} y^{\prime } = x y y^{\prime }
\] |
✓ |
✓ |
|
\[
{}2 x y y^{\prime } = x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {1+x -2 y}{2 x -4 y}
\] |
✓ |
✓ |
|
\[
{}\left (-x^{3}+1\right ) y^{\prime }+x^{2} y = x^{2} \left (-x^{3}+1\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+x +x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\left (\frac {1}{x}-\frac {2 x}{-x^{2}+1}\right ) y = \frac {1}{-x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+1\right ) y^{\prime }+x y = \left (x^{2}+1\right )^{{3}/{2}}
\] |
✓ |
✓ |
|
\[
{}x \left (1+y^{2}\right )-y \left (x^{2}+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {r \tan \left (\theta \right ) r^{\prime }}{a^{2}-r^{2}} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {y}{x} = x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-5 y = \left (x -1\right ) \sin \left (x \right )+\left (1+x \right ) \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-5 y = 3 \,{\mathrm e}^{x}-2 x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-5 y = {\mathrm e}^{x} x^{2}-x \,{\mathrm e}^{5 x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = {\mathrm e}^{2 x} x +1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-y = \sin \left (x \right )+\cos \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {4 y}{x} = x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {y}{x} = x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = 2
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 y = {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y
\] |
✓ |
✓ |
|
\[
{}y y^{\prime }+x = 0
\] |
✓ |
✓ |
|
\[
{}2 x^{3} y^{\prime } = y \left (y^{2}+3 x^{2}\right )
\] |
✓ |
✓ |
|
\[
{}4 y+x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+2 y+\left (-x^{2}+4\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1+y-\left (1+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|